Effects of low-dose γ-irradiation on the water state of fresh Lentinula edodes. (January 2020) - Shi, Defang; Zhou, Ranran; Feng, Xi; Dong, Xiaobo; Gao, Hong; Fan, Xiuzhi; Yin, Chaomin; Qiao, Yu; Liu, Ying; Huang, Wen
Abstract: Understanding the water state in fresh Lentinula edodes under low-dose irradiation will be helpful to evaluate the freshness and forecast the shelf-life. In this study, the effects of low-dose γ-irradiation (1.0 and 2.0 kGy) on the water state of L. edodes during storage were investigated. Low-field nuclear magnetic resonance results revealed that fractions M 22 and M 23 constituted the predominant parts among the four water fractions. The results also released that 1.0 kGy-irradiated mushrooms maintained the water state and good appearances. However, 2.0 kGy irradiation caused watery exudate and unfavourable appearance. Moreover, the changes of water state associated with the appearance can be used to assess the freshness and forecast the shelf-life of irradiated L. edodes . Our results suggested that low-dose γ-irradiation (≤1.0 kGy) was a potential preservative method to decrease the water loss, retain the freshness, and extend the shelf-life of fresh mushrooms. Highlights: Water state of fresh Lentinula edodes was studied during post-irradiation storage. Different low-dose irradiation treatments (1.0 and 2.0 kGy) influenced the water state. The behavior of water changes was able to assess freshness and shelf life of L. edodes. Low-dose γ-irradiation could reduce water loss and extend shelf-life of fresh mushrooms.